Become Recognized Minority in a Multicultural Society: An- Naim’s Theory in Responding to Ahmadiyyah Cases in Indonesia - Muta Ali Arauf (International Journal of Social Science and Religion (IJSSR), 2022)
This study  aims  to  analyze  the  thoughts  of  Abdullah  Ahmed  an-Naim  related  of  constitutionalism,  human rights and citizenship based on justice in minority groups.  An-Naim’s thoughts on human  rights  can  be  accommodated  to  public  expectations  regarding  the  issue  of  the  Ahmadiyya  community  in  Indonesia.  Read an-Naim’s theory regarding women,  non-Muslim  status  and  apostasy. The issue of human rights initiated by an-Naim will be the basic foundation in the explicit explanation of this paper. Considering the existing social values based on the enforcement of human rights in Indonesia, the position of the Ahmadiyya community must be positioned equally in the law in terms of rights and obligations as  part  of  Indonesian citizens. The state must be neutral considering the Ahmadiyya community in responding to its religious existence.  The government must maintain neutrality in regulating religious life for every citizen in order to create an atmosphere of harmony and peace. This paper attempts to produce a peaceful religious discourse in the context of religious freedom in Indonesia